#### Question

Inverse of the statement pattern (p ∨ q) → (p ∧ q) is

(A) (p ∧ q) → (p ∨ q)

(B) ∼ (p ∨ q) → (p ∧ q)

(C) (∼ p ∨ ∼ q) → (∼ p ∧ ∼ q)

(D) (∼ p ∧ ∼ q) → (∼ p ∨ ∼ q)

#### Solution

(D) (∼ p ∧ ∼ q) → (∼ p ∨ ∼ q)

statement pattern: (p ∨ q ) → ( p ∧ q)

Its inverse is

~ (p ∨ q ) → ~ ( p ∧ q)

≡ (∼ p ∧ ∼ q) → (∼ p ∨ ∼ q)

Is there an error in this question or solution?

#### APPEARS IN

Solution for question: Inverse of the statement pattern (p ∨ q) → (p ∧ q) is concept: Mathematical Logic - Sentences and Statement in Logic. For the courses HSC Arts, HSC Science (Electronics), HSC Science (General) , HSC Science (Computer Science)